Pengaruh Brand Equity dan Word Of Mouth terhadap Keputusan Pembelian Pop Mie di Sidoarjo - Irfan Wahyu Jatmiko; Ugy Soebiantoro (Politeknik Piksi Ganesha Indonesia, 2023)
This study explains how brand equity and word of mouth influence purchasing decisions for Pop Mie in Sidoarjo in the midst of the development of cup instant noodle products and the condition of Indonesian people who have a FOMO attitude. The research objective is to determine the effect of brand equity and word of mouth on purchasing decisions for Pop Mie in Sidoarjo. The research is quantitative, primary data is generated from distributing questionnaires using Google Form, secondary data from previous research journals, books, data from websites or trusted data survey institutions. The sample used was 100 samples, non probability sampling with convenience sampling technique was used in sampling. The data analysis technique uses PLS through the SmartPLS 4.0 program. This study found that there is a contribution of brand equity and word of mouth in purchasing decisions for Pop Mie in Sidoarjo.